Hubungan Kepatuhan Memakai Kacamata dengan Progresivitas Miopia pada Mahasiswa FK UNDIP - Kingwijati, Syahriza Naufal; Wildan, Arief; Dharma, Andhika Guna; Nugroho, Trilaksana (Majalah Oftalmologi Indonesia, 2023)
Introduction Myopia is a refractive error that causes images of distant objects to be focused in front of the retina by the non-accommodating eye. Myopia is one of the most common visual disturbances in the world. It is believed that the use of spectacle can reduce the progressivity rate of myopia. Spectacle can help light fall on the retina and prevent axial elongation of the eye. This theory needs to be investigated further so that it can be used as a reference. This study aimed to know the correlation between compliance of spectacle wear and myopia progressivity rate in medical students of Diponegoro University (UNDIP). Methods This research was an observational analytical study with cross-sectional design on 54 subjects ranging from 18 to 22 years old. Data are primary data obtained from questionnaires and objective eye examinations using an autorefractometer. The research was conducted from October to November 2021. Data were analyzed using Spearman Rank test which p<0,05 was considered significant. Results The mean of compliance of spectacle wear and myopia progressivity rate in medical students of UNDIP are (1,57±0,108) and (0,259±0,515) dioptres respectively. The correlation between compliance of spectacle wear and myopia progressivity rate are p=0,082 and r=0,239. Conclusion There are no correlation between compliance of spectacle wear and myopia progressivity rate in medical students of UNDIP. Keywords : Compliance, Spectacle, Myopia progressivity rate, Student